Some properties of magnetospheric electrons observed west of Sanae - Greener, James G (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1973)
The southern hemisphere has always been the neglected twin in the field ot geophysical research. The reasons for this are certainly not in the realm of science but in the history of man and his development in the northern half of the globe. Geophysically, however, our southern half provides a wealth of interesting problems and anomalies. Roederer (1966) explains the use of this word 'anomaly' by showing what some of the oddities of the southern hemisphere are, and by contrasting them with the corresponding regions of the earth across the equator. The principal feature is of course the geomagnetic surface field strength minimum at a point in the South Atlantic ocean very near the coast of Brazil. Intro., p. 1.
Keywords: Magnetosphere